Advances in mechanical engineering : selected contributions from the Conference "Modern Engineering: Science and Education", Saint Petersburg, Russia, June 2017 /: selected contributions from the Conference "Modern Engineering: Science and Education", Saint Petersburg, Russia, June 2017. ([2018]) - Unknown
No abstract available